GAGASAN KONSENTRASI PEMBIDANGAN PADA JURUSAN PENDIDIKAN AGAMA ISLAM DI FAKULTAS TARBIYAH PTAI - Muthohar, Ahmad (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2013)
Abstract: The idea of the program concentration was originated from public complaints of Madrasah users. They were less satisfied with the competence of the alumni who did not master the field of Islamic studies. Hence, Department of Islamic Education (PAI) ought to have strategic policies to establish new specific programs in accordance with the curriculum as a subjectÂ  in schools and Madrasah. UnlikeÂ  in public school that serves PAI as religious subject, Madrasah serves Al - Quran - Hadith, Aqidah Akhlaq, Fiqh and Islamic Cultural History. This should be responded by faculty to cope with the needs of Madrasah users by establishing the new programs such as: 1 ) Islamic Education ( PAI ), prepared to be a teacher of Islamic religion in schools, 2 ) Al - Qurâan-Hadith program, 3 ) Aqidah Akhlaq program, 4 ) Fiqh Program and ( 5 ) Cultural History of Islamic studies program, which are prepared to become the teachers in Madrasah.Â Ø¹ÙØªÙÙ Ù .Ø©ÙÙÙØ¯ÙØ§ Ø³Ø±Ø§Ø¯ÙØ§ ÙØ¬Ø±Ù Ø¹ÙØªÙØ§ ÙÙØ§ÙØ´ ÙØ¹ Ø©ØªØ§Ù Ø¯Ø§ÙÙØ§ ÙÙÙØµØª ÙÙØ¹ Ø²ÙÙØªÙØ§ Ø©Ø±ÙÙ ÙØ¥ :ØµØ®ÙÙÂ Ø©ÙÙÙ Ù(Â  Ø©ÙÙÙØ³ÙØ§Â  Ø©ÙØ¨ØªÙØ§Â  ÙØ³ÙÂ  ÙØ¥ÙÂ  Ø§Ø°ÙÂ  .Ø©ÙÙÙØ³ÙØ§Â  Ø¯Ø§ÙÙØ§Â  ÙÙØ¹ ÙÙÙÙØªØ³ÙÂ  Ù ÙÙØ°ÙØ§Â  ÙØ¬Ø±ÙØ§Â  Ø©Ø¡Ø§ÙÙØ¨Â  Ø¡ÙØ¤ÙÂ .Ø©ÙÙÙØ¯ÙØ§ Ø³Ø±Ø§Ø¯ÙØ§Ù )Ø©ÙØ§Ø¹( Ø³Ø±Ø§Ø¯ÙØ§ Ù ÙØ³Ø§Ø±Ø¯ÙØ§ Ø¬ÙÙÙØ§ Ø¨Ø³Ø§ÙØª ØªÙØ§ Ø©Ø¯ÙØ¯ÙØ§ ÙØ§Ø³ÙÙØ§ ØØ§ØªØªÙØ§ ÙÙÙØ¹ ÙØºØ¨ÙÙ )Ø©ÙØ¨ØªÙØ§Â Ø©Ø¯ÙÙØ¹ÙØ§Ù ØØ«ÙØ¯ÙØ§Ù ÙØ¢Ø±ÙÙØ§ Ø©Ø¯Ø§Ù Ø©ÙÙÙØ¯ÙØ§ Ø³Ø±Ø§Ø¯ÙØ§ ÙÙ ØØ©ÙÙÙØ³ÙØ§ Ø©ÙØ¨ØªÙØ§ Ø©Ø¯Ø§Ù )Ø©ÙÙÙØ¯ÙØ§ ÙØº( Ø³Ø±Ø§Ø¯ÙØ§ Ù ÙÙÙØªÂ Ø©ÙØ¨ØªÙØ§ ÙØ³Ù )1 : ÙÙ Ø§Ø¯ÙØ¯Ø¬ Ø§ÙØØ§ØªØªÙØ§ ÙØºØ¨ÙÙ ØªÙØ§ ÙØ§Ø³ÙÙØ§ ÙØ¥Ù ØØ©ÙÙÙØ³ÙØ§ Ø©ÙØ§ÙØ«ÙØ§ Ø®ÙØ±Ø§ØªÙ ÙÙÙÙØ§Ù ØÙÙØ®ÙØ§ÙÂ ÙØ³Ù )5 ØÙÙÙÙØ§ ÙØ³Ù )4 ØÙÙØ®ÙØ§Ù Ø©Ø¯ÙÙØ¹ÙØ§ Ø©Ø³Ø§Ø±Ø¯ ÙØ³Ù )3 ØØ©ÙØ«ÙØ¯ÙØ§Ù Ø©ÙÙØ§Ø±ÙÙØ§ Ø©Ø³Ø§Ø±Ø¯ÙØ§ ÙØ³Ù )2 ØØ©ÙÙÙØ³ÙØ§Â .Ø©ÙÙÙØ¯ÙØ§ Ø³Ø±Ø§Ø¯ÙØ§ Ù ÙØ³Ø±Ø¯Ù ÙØ¨ÙØªØ³ÙØ§ Ù Ø¨ÙØ·ÙØ§ ÙÙÙÙÙ ØØ©ÙÙÙØ³ÙØ§ Ø©ÙØ§ÙØ«ÙØ§ Ø®ÙØ±Ø§Øª